Effects of climate warming on photosynthesis in boreal tree species depend on soil moisture. (11th October 2018) - Reich, Peter; Sendall, Kerrie; Stefanski, Artur; Rich, Roy; Hobbie, Sarah; Montgomery, Rebecca
Abstract Climate warming will influence photosynthesis via thermal effects and by altering soil moisture1–11 . Both effects may be important for the vast areas of global forests that fluctuate between periods when cool temperatures limit photosynthesis and periods when soil moisture may be limiting to carbon gain4–6, 9–11 . Here we show that the effects of climate warming flip from positive to negative as southern boreal forests transition from rainy to modestly dry periods during the growing season. In a three-year open-air warming experiment with juveniles of 11 temperate and boreal tree species, an increase of 3.4 °C in temperature increased light-saturated net photosynthesis and leaf diffusive conductance on average on the one-third of days with the wettest soils. In all 11 species, leaf diffusive conductance and, as a result, light-saturated net photosynthesis decreased during dry spells, and did so more sharply in warmed plants than in plants at ambient temperatures. Consequently, across the 11 species, warming reduced light-saturated net photosynthesis on the two-thirds of days with driest soils. Thus, low soil moisture may reduce, or even reverse, the potential benefits of climate warming on photosynthesis in mesic, seasonally cold environments, both during drought and in regularly occurring, modestly dry periods during the growing season. Low soil moisture may reduce, or even reverse, the potential benefits of climate warming on photosynthesis in mesic, seasonally cold environments, both during drought and in regularly occurring, modestly dry periods during the growing season.